2019
DOI: 10.1038/s41370-019-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sociodemographic characteristics and exposures to PBDEs, OH-PBDEs, PCBs, and PFASs in a diverse, overweight population of pregnant women

Abstract: Exposures to persistent organohalogen chemicals during pregnancy are associated with adverse health effects. Low-income, minority women with pre-existing co-morbidities may be particularly vulnerable to these exposures, but have historically been understudied. We aimed to characterize exposures to multiple chemical classes among a sample of ethnically diverse, lower income, overweight or obese pregnant women. Serum concentrations of polybrominated diphenyl ethers (PBDEs) and their hydroxylated metabolites (OH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 63 publications
(86 reference statements)
0
37
0
Order By: Relevance
“…As demonstrated by research studies of pregnant women from Denmark and Mexico [18,19], it is a POP with a low detection level. Studies from North America, where concentrations of PBDEs are known to be greater than in other parts of the world, have, however, found concentrations of various PBDE to increase with pre-pregnancy BMI and have suggested that PBDEs may have an obesogenic effect and accelerate the proliferation of adipose cells [25,35]. It can also be noted that, compared to PCBs, PBDEs represent a 'younger' class of POPs and could therefore have a different distribution in the body than PCBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As demonstrated by research studies of pregnant women from Denmark and Mexico [18,19], it is a POP with a low detection level. Studies from North America, where concentrations of PBDEs are known to be greater than in other parts of the world, have, however, found concentrations of various PBDE to increase with pre-pregnancy BMI and have suggested that PBDEs may have an obesogenic effect and accelerate the proliferation of adipose cells [25,35]. It can also be noted that, compared to PCBs, PBDEs represent a 'younger' class of POPs and could therefore have a different distribution in the body than PCBs.…”
Section: Discussionmentioning
confidence: 99%
“…Censored regressions are the preferred approach to analyze datasets with an important number of censored observations (i.e., low-level concentrations of POPs with values known to be between zero and the laboratory's LOD) [25]. Unadjusted and adjusted censored regression models were used to estimate beta (β) coe cients with corresponding 95% con dence intervals of the relationships between rst trimester BMI and lipid-adjusted POPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another popular technique that has been used to study gestational mixtures is hierarchical clustering, a dimension reduction technique by which chemical exposures can be partitioned into groups. 6,64 For example, in 2020, Mehta et al 16 used hierarchical clustering and PCA to study associations between gestational exposure mixtures and sociodemographic variables. Like with latent profile analysis, this method does not require one to predetermine the number of groups; however, a key difference is that in this study, the researchers partitioned exposure variables, whereas we were interested in clustering the participants to find associations with chemical mixtures as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…After PBDEs undergoing phase I metabolism, hydroxylated polybrominated diphenyl ethers (OH-PBDEs) metabolites formed in animals, which may cause more severe biological effects [ 23 ]. OH-PBDEs are new type of organic pollutant, and have gradually become a new hotspot for environmental research field [ 24 , 25 ]. Besides, the study indicated that 2-OH-BDE85 has stronger dose-dependent toxicity than 2-OH-BDE47 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%